The Influence of the Probing Prompting Model on Students’ Mathematics Learning Outcomes at SDN 2 Kayangan - Yunita, Elma; Sukarto, Sukarto; Rahayu, Eka Pamuji (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to describe whether there is an influence of the Probing Prompting Model on the Mathematics Learning Outcomes of Grade 4 Students at SDN 2 Kayangan. This research was carried out at SDN 2 Kayangan on class 4 students in the second semester of the 2023/2024 academic year. The method used in this research is quantitative with a quasi-experimental method in the form of Pretest-Posttest Group Design. The population in this study were 4th grade students at SDN 2 Kayangan. The sample for this research consisted of 26 students. Data collection techniques use tests and documentation and data collection instruments use pre-test and post-test. The validity of this research uses validity tests and reliability tests. The data analysis technique uses descriptive analysis, the normality test uses (Klomogrov Smirnov Test) and the homogeneity test uses (Lavene Test). Meanwhile, hypothesis testing uses the T-test or T-Test which produces tcount 13,832 > ttable 0.388 which proves that there is an influence of the probing prompting model on mathematics learning outcomes.